2004
DOI: 10.1111/j.1364-3703.2004.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐dependent differences during synergistic infection by Potyviruses with potato virus X

Abstract: SUMMARY A comparative analysis of the synergistic interaction between PVX and either PVY or TEV potyviruses was performed in Nicotiana benthamiana and N. tabacum plants. In each PVX/potyvirus combination, doubly infected plants developed much more severe symptoms than singly infected ones. However, while PVX accumulation increased in doubly infected N. tabacum plants compared with singly infected plants, the accumulation of PVX did not vary drastically in doubly infected N. benthamiana plants with respect to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 33 publications
4
37
0
4
Order By: Relevance
“…Synergy is often manifested by a remarkable increase in both virus accumulation and symptom expression, compared to single infections. The beststudied synergistic interaction involves Potato virus X (PVX) with a number of potyviruses in tobacco (Nicotiana tabacum) plants, in which the level of PVX is enhanced severalfold compared to its level in singly infected plants (16,17). Potyvirus-associated synergistic diseases have been suggested to result from suppression of the host defense mechanism based on RNA silencing by the potyviral VSR, helper component-proteinase (HC) protein (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Synergy is often manifested by a remarkable increase in both virus accumulation and symptom expression, compared to single infections. The beststudied synergistic interaction involves Potato virus X (PVX) with a number of potyviruses in tobacco (Nicotiana tabacum) plants, in which the level of PVX is enhanced severalfold compared to its level in singly infected plants (16,17). Potyvirus-associated synergistic diseases have been suggested to result from suppression of the host defense mechanism based on RNA silencing by the potyviral VSR, helper component-proteinase (HC) protein (18).…”
mentioning
confidence: 99%
“…Potyvirus-associated synergistic diseases have been suggested to result from suppression of the host defense mechanism based on RNA silencing by the potyviral VSR, helper component-proteinase (HC) protein (18). However, the accumulation of PVX genomic RNA (gRNA) did not increase greatly in N. benthamiana when doubly infected with PVX and either Plum pox virus (PPV) or Tobacco etch virus (TEV), despite the extreme enhancement of symptoms in this host that lead to SN, i.e., synergism in pathology (16,19). PVX-mediated expression of viral genes to determine whether a protein would function as a pathogenicity determinant is a wellestablished technique (17,20).…”
mentioning
confidence: 99%
“…Previous studies showed an increase of PVX in mixed infection of PVY and PVX compared to the single inoculations [32,40]. Whereas, González-Jara et al [11] reported that PVY and PVX mixed infection did not cause a considerable increase in the accumulation of PVX in N. benthamiana though the severe symptoms like necrosis of leaves and stems leading up to the death of plants. Similar observations were also reported for PVX in mixed infections with O and NTN strain of PVY [29].…”
Section: Discussionmentioning
confidence: 88%
“…N. benthamiana plants were grown in a growth chamber with a 16-h-light/8-h-dark cycle at 25°C. Four-week-old N. benthamiana plants were inoculated by rubbing plant sap infected with PVX, PVY, or Tomato spotted wilt virus (TSWV) onto two fully expanded leaves as described previously (33). Mixed inoculations were performed separately on opposite halves of the same leaves.…”
Section: Methodsmentioning
confidence: 99%